The Urgency of the Principle of Balance in the Drafting of the Consumer Protection Bill - Mifahul Zannati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the urgency of the principle of balance in the drafting of the Indonesian Consumer Protection Bill (RUU-PK). The principle of balance is essential to ensure fairness and legal certainty among consumers, business actors, and the government, especially in modern digital transactions such as e-commerce. Using normative legal research with a literature-based approach, this study analyzes statutory regulations, legal literature, and comparative cases. The results show that the principle of balance must be strengthened in the RUU-PK to address structural inequalities in the digital economy. A comparison between the current Consumer Protection Law (UU No. 8/1999) and the draft bill reveals that the RUU-PK seeks to clarify rights and obligations, introduce joint liability mechanisms, and enhance government oversight. The study concludes that the principle of balance is the foundation for a just, transparent, and sustainable trade ecosystem in Indonesia.